Mempelajari Karakteristik Pengeringan Kerupuk Sayur - Annie Widya Subagya; Tamrin Tamrin; Cicih Sugianti; Diding Suhandy (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2018)
Crackers is one of the popular food products among the people of Indonesia. The addition of cassava leaves into crackers take advantage of the availability of cassava leaves, especially during harvesting. The research aims to determine some parameters of drying characteristics of vegetable crackers. Drying crackers were conducted using sun drying and rack dryers with the temperature of 50 °C and crackers’s thickness of 2 mm, 3 mm, and 4 mm. The results showed that drying using dryer with cracker’s thickness of 2 mm, 3 mm, and 4 mm spent a drying time about 3.5-4.5 hours that was faster than sun drying around 4.5 – 5.5 hours. The decrease of moisture content in the dryer was quicker than sun drying. The final moisture content of cracker using dryer had average value of 8.28% which was lower than the sun drying of 12.95% . The color changes that occured after the drying process using dryer and sun drying produced value <0.5 which had a meaningless or unchanged after the drying process. Depreciation of material diameter on dryers had a value of 11.92% which was greater than sun drying. The mean of moisture balance (Me) in the dryer of 7.348 %bb was lower than using sun drying. Drying constant of creackers value using dryer had an average value of 1.196 /hours that was higher than the sun drying 0.84 /hour.